Prospection and emotional memory: how expectation affects emotional memory formation following sleep and wake - Cunningham, Tony J.; Chambers, Alexis M.; Payne, Jessica D. (Frontiers in Psychology, 2014)
Successful prospective memory is necessarily driven by an expectation that encoded information will be relevant in the future, leading to its preferential placement in memory storage. Like expectation, emotional salience is another type of cue that benefits human memory formation. Although separate lines of research suggest that both emotional information and information explicitly expected to be important in the future benefit memory consolidation, it is unknown how expectation affects the processing of emotional information and whether sleep, which is known to maximize memory consolidation, plays a critical role. The purpose of this study was to investigate how expectation would impact the consolidation of emotionally salient content, and whether this impact would differ across delays of sleep and wake. Participants encoded scenes containing an emotionally charged negative or neutral foreground object placed on a plausible neutral background. After encoding, half of the participants were informed they would later be tested on the scenes (expected condition), while the other half received no information about the test (unexpected condition). At recognition, following a 12-hour delay of sleep or wakefulness, the scene components (objects and backgrounds) were presented separately and one at a time, and participants were asked to determine if each component was old or new. Results revealed a greater disparity for memory of negative objects over their paired neutral backgrounds for both the sleep and wake groups when the memory test was expected compared to when it was unexpected, while neutral memory remained unchanged. Analyzing each group separately, the wake group showed a threefold increase in the magnitude of this object/background trade-off for emotional scenes when the memory test was expected compared to when it was unexpected, while those who slept performed similarly across conditions. These results suggest that emotional salience and expectation cues inter